Pancreatoduodenectomy at the Verona Pancreas Institute: the Evolution of Indications, Surgical Techniques, and Outcomes: A Retrospective Analysis of 3000 Consecutive Cases. Issue 6 (15th December 2022) - Bassi, Claudio; Marchegiani, Giovanni; Giuliani, Tommaso; Di Gioia, Anthony; Andrianello, Stefano; Zingaretti, Caterina Costanza; Brentegani, Giacomo; De Pastena, Matteo; Fontana, Martina; Pea, Antonio; Paiella, Salvatore; Malleo, Giuseppe; et al.
Abstract : Objective: The aim of the present study was to critically reappraise the experience at our high-volume institution to obtain new insights for future directions. Summary Background Data: The indications, surgical techniques, and perioperative management of pancreatoduodenectomy (PD) have profoundly evolved over the last 20 years. Methods: All consecutive PDs performed during the last 20 years at the Verona Pancreas Institute were divided into four 5-year timeframes and retrospectively analyzed in terms of indications, intraoperative features, and surgical outcomes. Significant milestones were provided to understand practice changes using a before-after analysis method. Results: The study population consisted of 3000 patients. The median age, ASA ≥ 3 and number of nonbenchmark cases significantly increased over time ( P < 0.005). Pancreatic cancer was the leading indication, representing 60% of patients/year in the last timeframe, 40% of whom received neoadjuvant treatment. Conversely, after the development of International Guidelines, the proportion of resected cystic neoplasms progressively and thoroughly decreased. Given the increased complexity of surgery for pancreatic cancer, the evolution of technologies, surgical techniques, and postoperative management allowed the maintenance of favorable surgical outcomes over time, with a stable 20.0% of patients with a Clavien-Dindo grade ≥ 3, an 11.7% failure to rescue and a 2.3% in-hospital mortality rate. The incidence of postoperative pancreatic fistula, hemorrhage, and delayed gastric emptying was 22.4%, 13.4%, and 12.4%, respectively. Conclusions: PD significantly evolved in Verona over the past 2 decades. Surgeries of greater complexity are currently performed on increasingly frailer patients, mostly for pancreatic cancer and often after neoadjuvant chemotherapy. However, the progression of all fields of pancreatic surgery, including the expanding use of postoperative pancreatic fistula mitigation strategies, has allowed satisfactory outcomes to be maintained.